Greenery Effects: Comparing the Associations Between Multi-Dimensional Measurements of Urban Green Space Greenery and Engagement in Health-Related Activities Across Age Groups - Chongxiao Wang; Shuolei Chen; Yang Chen; Zhongzhe Shen (Land, 2025)
With the progression of global urbanization, UGS greenery plays an increasingly important role in encouraging engagement in various health-related activities among sedentary residents, and its quality improvement is widely recognized as a promising strategy for achieving public health benefits. However, existing studies have not reached an agreement on the associations between UGS greenery and engagement in health-related activities, largely due to limited dimensions of greenery measurement and insufficient evidence on health-related activities. To address these gaps, this study proposes a holistic analytical framework that integrates multi-dimensional greenery measurements (measured by the NDVI, GVI, and LVV metrics) with systematic observations of engagement in physical activity and social interaction across the general population, children, and seniors, allowing for a more comprehensive understanding of their varied associations. Conducting empirical research in the Xuanwu Lake Scenic Area, the results showed that (1) UGS greenery had stronger explanatory power for activity participant numbers than activity intensity across age groups; (2) top–down greenery (NDVI) was positively associated with engagement in health-related activities (although not statistically significant), while excessive eye-level (GVI) and spatial greenery (LVV) demonstrated negative effects; (3) UGS greenery alone did not sufficiently predict children’s engagement in health-related activities; and (4) greenery conditions in adjacent UGS samples also significantly impacted local health-related activities. These findings suggest that UGS greenery measured from a single dimension may not reliably predict engagement in health-related activities across age groups, thereby calling for balanced and context-sensitive greenery design in future UGS planning to support inclusive public health.